A Peptide-Based Enzyme-Linked Immunosorbent Assay for Detecting Antibodies Against Avian Infectious Bronchitis Virus - Yin, Liping; Wu, Qi; Lin, Zhixian; Qian, Kun; Shao, Hongxia; Wan, Zhimin; Liu, Yuelong; Ye, Jianqiang; Qin, Aijian (Frontiers in Veterinary Science, 2021)
Infectious bronchitis virus (IBV) causes substantial loss to the poultry industry despite extensive vaccination. Assessing the antibody response is important for the development and evaluation of effective vaccines. We have developed an enzyme-linked immunosorbent assay (ELISA) for the detection of IBV-specific antibodies, using a synthetic peptide based on a conserved sequence in the IBV spike protein. This peptide-based ELISA (pELISA) specifically detects antibodies to different genotypes of IBV but not antibodies against other common chicken viruses. This assay is could detect IBV-specific antibody response on as early as day 7 post infection. In the testing with field serum samples collected from chickens administered with IBV vaccines, the sensitivity, specificity and accuracy of pELISA were 98.30%, 94.12% and 98.8%, respectively, relative to indirect immunofluorescence assay. Our data demonstrate that the pELISA is of value for the detection of IBV antibody and the evaluation of IBV vaccines.